Development of an allocation model for surface runoff management using mixed-integer linear programming: A case study of Binahaan catchment - Genoguin, Marvin Jade G. (Animo Repository, 2023)
Flood mitigation is one of the top priorities in water resources management. Flooding has been a problem over the millennia, and despite the effectiveness of the current flood- mitigating solutions, the problem is still on the rise. The impacts of flooding affect the economic and social aspects of people, leaving them vulnerable. That is why it is imperative that proper flood management should be done to combat this problem. Most current allocation model studies focus more on water allocation under water scarcity. Floodwater allocation, however, is done in an abundance of water. The recent floodwater allocation studies are too complex because of their multiple time steps, thus, requiring a tremendous amount of data and being computationally expensive. Therefore, this paper provides a model that allocates flood water with only a single time step but achieves the desired results. This study proposes developing an allocation model that can reduce the effects of flood damage by allocating surface water runoff to current demands and sinks. The proposed model is also designed to add a reservoir if the sub-catchment can no longer hold the excess runoff. The model developed was used in a case study in the Binahaan catchment, where irrigation was used as an existing demand. Only sub-catchment 9 (SB9) activated the additional reservoir among all the sub- catchments (SBs). This is because irrigation demand in SB9 could not contain all surface runoff during all three return periods. In addition, all SBs, except SB9 and SB12, could contain surface runoff for all three return periods, eliminating the need for an additional reservoir. Results show that the model can successfully allocate the surface water runoff to the current demands (i.e., irrigation) and propose an additional reservoir if the demand cannot accommodate the excess runoff. Results also show that effective allocation to the existing demands alone can mitigate floods without additional reservoirs.